2010
DOI: 10.2202/1949-6605.6056
|View full text |Cite
|
Sign up to set email alerts
|

“We Just Don't Have the Possibility Yet”: U.S. Latina/o Narratives on Study Abroad

Abstract: Jeffrey Reed, United States Naval Academy Whether indirectly from governmental and non-governmental organizations or directly from higher education institutions, students receive messages that they should study abroad. Studying in a foreign country is considered essential if students are to be marketable to future employers and prepared to lead the U.S. into a new era. Despite the presence of such messages, the understanding of what it means to be absent from the undergraduate student population willing and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 4 publications
0
31
1
Order By: Relevance
“…Chieffo (2001), among others, indicates that students in certain major fields of study are less likely to study abroad. Researchers have found that students mention scheduling conflicts and conflicts with major requirements as a primary reason for not studying abroad (Wainwright, Ram, Teodorescu, & Tottenham, 2009), and students are often concerned that studying abroad will slow their academic progress towards degree completion (McClure, Szelenyi, Niehaus, Anderson, & Reed, 2010). Wainwright et al (2009) additionally point out a lack of faculty support for study abroad in many cases, especially among students in science fields.…”
Section: Conceptual Framework: Barriers and Counter -Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Chieffo (2001), among others, indicates that students in certain major fields of study are less likely to study abroad. Researchers have found that students mention scheduling conflicts and conflicts with major requirements as a primary reason for not studying abroad (Wainwright, Ram, Teodorescu, & Tottenham, 2009), and students are often concerned that studying abroad will slow their academic progress towards degree completion (McClure, Szelenyi, Niehaus, Anderson, & Reed, 2010). Wainwright et al (2009) additionally point out a lack of faculty support for study abroad in many cases, especially among students in science fields.…”
Section: Conceptual Framework: Barriers and Counter -Barriersmentioning
confidence: 99%
“…On the positive, supportive policies enable students to plan their abroad experience multiple years in advance (McClure et al, 2010) and provide students with opportunities to leverage capital resources for the purpose of study abroad participation. Literature on the role of institutional programs designed for success at community colleges (Hodara & Jaggars, 2014;Roksa & Kinsley, 2019) clearly demonstrates that non-traditional students use their capitals to achieve a range of success (Kruse, Starobin, Chen, Baul, & Laanan, 2015;Moschetti & Hudley, 2015;Yosso, 2005).…”
Section: Institutional Policies and Practicesmentioning
confidence: 99%
“…(Stroud 2010: 493) Though a number of task forces, coalitions, special interest groups and scholarship programs have been created to address the underrepresentation of racial/ ethnic minority student in U.S. study abroad, the gains such efforts have produced in the enrollment and representation of these students in study abroad have been described as "very disheartening" (Shih 2009). This "disheartening" level of participation has been attributed to a number of factors: lack of information about study abroad and the process of applying to programs (Van Der Meid 2003;Shih 2009;Brux and Fry 2010;McClure et al 2010;Stallman et al 2010); lack of structural support/encouragement from faculty and other peers (Cole 1991;Washington 1998;Perdreau 2000;Penn and Tanner 2009;Shih 2009; Brux and Fry 2010; Bruce 2012; Simon and Ainsworth 2012); lack of motivation/limited commitment to international education on the part of students (Brown 2002;Van Der Meid 2003;Dessoff 2006;Shih 2009; Brux and Fry 2010; Salisbury et al 2011); inadequate preparation in foreign languages/curricular requirements on campus (Van Der Meid 2003); cultural barriers/fears of racism (Desruisseaux 1992;Hembroff and Rusz 1993;Carroll 1996;Craig 1998;Perdreau 2000;Brown 2002;Jackson 2005;Redden 2008;Brux and Fry 2010;Gaines 2012) and funding concerns (CIEE 1988;Cole 1991;Hembroff & Rusz 1993;Washington, 1998;NAFSA 2003;Dessoff 2006, Redden 2008Shih 2009;…”
Section: Coming To Know a Thing 21 Promoting And Democratizing Usmentioning
confidence: 99%
“…Wilson-Oyelaran 2011) or 2) at percentages comparable to their percentage of enrollment in U.S. higher education (Washington 1998;The Lincoln Commission 2005;Kasravi 2009;Picard et al 2009;Shih 2009;McClure 2010;Wilson-Oyelaran 2011). This latter pattern of framing differences in study abroad participation levels is observed in the following quote:…”
Section: Uniquely and Specifically A Minority Problemmentioning
confidence: 99%
“…Yet in‐depth theorisation of social relations of difference, such as race and class, are still scarce in global education. There is some acknowledgement that international mobility is an activity largely enjoyed by privileged students (Findlay et al., ; King et al., ; McClure et al., ; Waters, ). Aside from this recognition of the elitism of global education, our current analyses of young people's global experiences remain centred around neoliberalism and the assumption that young people engage in global education with the intention of becoming competitive economic citizens, focused on their own success, or at the very most, on maintaining their families’ privilege.…”
Section: Introductionmentioning
confidence: 99%